Gender Analysis of Prostitution Localization Closure Policy in Jember Regency - Friscilia Vita Anggraeni; Emy Kholifah Rachmaningsih (Eduvest - Journal of Universal Studies, 2026)
This study critically explores the policy on the closure of prostitution areas in Jember Regency through a gender equity lens. The policy, established under Regional Regulation No. 14 of 2001 and Regent's Decree No. 188.45/39/012/2007, was grounded in moral considerations and supported by public demand. Nevertheless, its implementation has produced unintended consequences, particularly for former female sex workers who have lost their primary source of income, experienced persistent social stigma, and encountered limited access to empowerment programs designed to support their transition into alternative livelihoods. Using a qualitative descriptive approach, this research draws on interviews, observations, and document analysis. The data were examined through Miles and Huberman's interactive analysis model. The study adopts Caroline Moser's (1993) Gender Analysis Pathway to assess four key dimensions: access, participation, control, and benefits, while William N. Dunn's (2015) policy analysis framework is applied to evaluate the rationality and substance of the policy. The findings suggest that the closure policy has yet to embody the principles of gender equity. Former sex workers face reduced access to economic opportunities and information, are not meaningfully involved in policy processes, have limited control over their economic choices, and receive insufficient benefits due to weak program implementation. These conditions indicate a gap between policy intentions and practical outcomes. Therefore, this study advocates for a more inclusive and gender-responsive policy reformulation, emphasizing integrated rehabilitation efforts, vocational skill development, and sustained economic support to ensure long-term social and economic reintegration for affected women.